The Effect of Different Types of Corrective Feedback on EFL Learners’ Accuracy in Using English Articles by the Eleventh Grade Science Students of SMA N 3 Bontang - Priswalia Anggariana Putri; Dyah Sunggingwati; Satyawati Surya (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
This article reports on a study that investigated the effectiveness of direct-focused corrective feedback and metalinguistic focused feedback on EFL learners’ accuracy in using English articles. The study employed a pretest–posttest design with five treatment sessions. The design of this study was quasi-experimental design. The sample of this study were 60 of the eleventh grade science students. They were assigned into two groups, direct-focused corrective feedback group and metalinguistic-focused feedback group. The linguistic target was English articles. A fill in the blank exercise were employed to measure any development in learners’ ability to use articles. The results revealed that both direct-focused corrective feedback and metalinguistic focused feedback lead to greater learners’ accuracy of using English articles. The direct-focused feedback is found more effective than metalinguistic-focused feedback.